Genetic structure of the widespread and common Mediterranean bryophyte Pleurochaete squarrosa (Brid.) Lindb. (Pottiaceae): evidence from nuclear and plastidic DNA sequence variation and allozymes - Grundmann, Michael; Koch, Marcus (Molecular ecology, 2007)
The Mediterranean Basin as one the world's most biologically diverse regions provides an interesting area for the study of plant evolution and spatial structure in plant populations. The dioecious moss Pleurochaete squarrosa is a widespread and common bryophyte in the Mediterranean Basin. Thirty populations were sampled for a study on molecular diversity and genetic structure, covering most major islands and mainland populations from Europe and Africa. A significant decline in nuclear and chloroplast sequence and allozyme variation within populations from west to east was observed. While DNA sequence data showed patterns of isolation by distance, allozyme markers did not. Instead, their considerable interpopulation genetic differentiation appeared to be unrelated to geographic distance. Similar high values for coefficients of gene diversity (GST) in all data sets provided evidence of geographic isolation and limited gene flow among populations (i) within islands, (ii) within mainland areas, and (iii) between islands and mainland. Notably, populations in continental Spain are strongly genetically isolated from all other investigated areas. Surprisingly, there was no difference in gene diversity and GST between islands and mainland areas. Thus, we conclude that large Mediterranean islands may function as ‘mainland’ for bryophytes. This hypothesis and its implication for conservation biology of cryptogamic plants warrant further investigation. While sexually reproducing populations were found all over the Mediterranean Basin, high levels of multilocus linkage disequilibrium provide evidence of mainly vegetative propagation even in populations where sexual reproduction was observed.